AGRONOMIC CHARACTERISTICS OF OREGANO (ORIGANUM SPP.) SPECIES COMMONLY FOUND IN THE FLORA OF ANTALYA - Turgut, K.; Tugrul Ay, S. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
In this study, some agronomic traits of Origanum species (O. saccatum, O. solymicum, O. majorana, O. onites and O. vulgare subsp. hirtum) collected from the natural flora of Antalya were investigated. The Origanum plants were propagated by stem cuttings from collection garden and planted at the experimental field with three replicates “Randomized Complete Plot Design”. In this research, green and dry herbage yield (kg/da), plant heigth (cm), branch number (number/plant) and essential oil yield (kg/da) of species were investigated. Air-dried aerial parts of the plants were subjected to hydrodistillation for 3 h using a Clevenger-type apparatus. The percentage yields of the oils were calculated on a dry weight basis. The research results showed that O. saccatum gave the highest mean values on plant height (64.8 cm), branch number (56.8), green and dry herbage yield (834.3 and 382.0 kg/da, respectively) and essential oil yield (11.5 l/da). In terms of essential oil yield, O. onites (7.6 l/da) and O. majorana (7.1 l/da) statistically made up second group and followed by O. vulgare subsp. hirtum (2.4 l/da) and O. solymicum (0.7 l/da). After all, O. saccatum appeared to be good candidate for breeding and cultivation studies. Acknowledgements: Funded by Akdeniz University Scientific Research Project Unit